Islamic Work Ethics, Organizational Culture, and Performance: The Mediating Role of Organizational Commitment - Syamsuarni, Syamsuarni; Mus, Abdul Rahman; Amang, Baso; Budiandriani, Budiandriani (International Review of Management and Marketing, 2026)
This study aims to analyze the influence of Islamic work ethics and organizational culture on the performance of Family Welfare Empowerment (PKK) cadres in Banggai Regency, with organizational commitment acting as a mediating variable. This research is motivated by the importance of improving the performance of PKK cadres as partners of the government in community empowerment and family welfare development. Islamic work ethics and organizational culture are considered important factors that can strengthen organizational commitment and improve the performance of cadres in implementing PKK programs. This study employs a quantitative approach using a survey method. The research population consists of PKK cadres in Banggai Regency, and the sample was determined using a sampling technique representing the population. Data were collected through questionnaires and analyzed using descriptive analysis and inferential analysis with a Structural Equation Modeling (SEM) approach. The results indicate that Islamic work ethics and organizational culture have a positive and significant effect on organizational commitment. Furthermore, Islamic work ethics, organizational culture, and organizational commitment positively influence the performance of PKK cadres. Organizational commitment is proven to act as a mediating variable that strengthens the relationship between Islamic work ethics and organizational culture and the performance of PKK cadres. These findings suggest that stronger implementation of Islamic work ethics and organizational culture leads to higher organizational commitment, which ultimately enhances the performance of PKK cadres. This study contributes theoretically to the development of human resource management, particularly within community organizations, and provides practical implications for PKK organizational management in improving cadre performance through strengthening Islamic work ethics, organizational culture, and organizational commitment.